(untitled) (Annals of Medical Research, 2022)
Aim: Pressure ulcers develop frequently in immobile elderly. Pressure is extrinsic factor and ıt plays a major role in ulcer development. Nurses use a pressure ulcer risk assessment tools and risk assessment effectives as a means to ulcers preventing. To determine frequency and predictive value of interface pressure in pressure ulcer development in elderly patients hospitalized in internal medicine intensive care units. Materials and Methods: The study involved 140 patients admitted to internal intensive care clinics between April 2018 and August 2018 without pressure ulcers and who stayed in the ICU for more than 72 hours. Participants were scored using the Braden scale and were examined for the risk level of pressure ulcers. The inclusion criteria were age over 65 years and having a high risk of developing pressing ulcers. Patients were evaluated by “Questionnaire Form,“Braden Risk Assessment Scale” and “Palm Q-Portable Interface Pressure Sensor” every two days during their stay in the clinic. Results: Pressure ulcer developed in 22.1% of the patients but it didn’t develop in any of the oral feeding patients. The mean time for ulcer to develop was 6.90±2.9 days. In patients with pressure ulcers, while the mean interface pressure value was 47.75±6.79 mmHg at the beginning of the final evaluation position, 51.25± 6.71mmHg at the end of the position. Conclusion: In all interface pressure measurements of patients who developed pressure ulcer, the interface pressure values increased at the end of the position compared to the beginning of the position.